ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINDAKAN TIDAK AMAN (UNSAFE ACT) PADA PELAKU SELFIE DIATAS GEDUNG BERTINGKAT JAKARTA - Fyka Ferziandhani; Bina Kurniawan; Ekawati Ekawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Self-portrait (selfie) change into a phenomenal act in the present era. In the List of selfie-related injuries and deaths, there are 23 people injured and died in 2015 and 9 people died up to March 2016. Most of the case caused by fall down while taking selfies on high level building. Selfie on the height building usually have no permission and not comply with the requirement of working at height. Those are no suit with “Undang-Undang No 1 Tahun 1970” which mention everyone who entered the workplace, are required to comply with all existing safety instructions. Not obeying the rules that already exist, including the unsafe act. The purpose of this study was determine the factors that influence unsafe act of selfie permormer on high level buildings in Jakarta. This research used descriptive method with qualitative approach. Three people participated in this research as key informants and two others as informants triangulation. The result showed the informant was having the right knowledge. However informant break the rules and trespass to climb up to high level building without permission. Informant always try yo be careful, they know what they are doing is dangerous, but they neglected it. The entire informants have gadgets such as cameras and sosical media and they have so many followers to support them and the informant’s friend to encourage them to making selfies above high level buildings. Informants usually seek in advance the condition of security on a building that will be climed. Role of the building management is very needed in the regulatory process. Individual behavior will change and follow the rules and instructions that apply.